Poverty and gender in the eastern gangetic plains of Nepal: Challenges and opportunities - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2017)
The majority of farmers of the Tarai-Madhesh region in Nepal struggle to make a living from low-productivity small-holdings, in a context of growing climate variability. This is a region with persistent rural poverty and deep inequalities in the distribution of resources, combined with a lack of opportunities in the local economy. This has induced significant outmigration, mostly of young men, resulting in the so-called “feminization” of the agriculture sector. While this has offered some limited economic empowerment, it does not necessarily transform gender relationships in relation to agriculture and water management in the region. Furthermore, a review of two major irrigation-related initiatives show that these development initiatives are not tackling the huge gender inequalities in the region, despite contrary claims from the donor and government (e.g. 2013 Nepal’s Irrigation Policy). More proactive steps are needed, such as support to women’s organizations and favorable grant conditions for women, to truly enable women’s empowerment in agriculture.